Маршал Рокоссовский: [12+] / Владимир Дайнес - Дайнес Владимир Оттович (Кавалеры ордена "Победа", 2015)
Экземпляры: ф. 7 (20150619) / Инвентарный номер: 50376 / Цена: 150.00 / Авт.знак: Д 14 / ГРНТИ: 03 / ББК: 63.3(2)622.78